Endogenous growth with deferred technological change - Pedroni, Marcelo Zouain (2009)
Lucas (2009) has proposed a two-sector model to account for patterns in growth data. However, Lucas’s analysis does not involve any inter-temporal decision by the consumers. The behavior of the variables is determined a priori by the technology that is chosen. Rodriguez (2006) proposed a model with the twosector technology presented by Lucas adding an inter-temporal decision process for the consumer. In addition to the results obtained by Rodriguez, we characterize sufficiency and provide elucidating examples of particular cases of the model. Moreover, we make an effort to derive new insights from the model and clarify some technical points. Finally, we obtain conditions under which the economy invests in human capital even though benefits are deferred.